Qualification and Application of a Liquid Chromatography-Quadrupole Time-of-Flight Mass Spectrometric Method for the Determination of Adalimumab in Rat Plasma - Park, Yuri (Pharmaceutics, 2018)
A liquid chromatography–quadrupole time-of-flight (Q-TOF) mass spectrometric method was developed for early-stage research on adalimumab in rats. The method consisted of immunoprecipitation followed by tryptic digestion for sample preparation and LC-QTOF-MS/MS analysis of specific signature peptides of adalimumab in the positive ion mode using electrospray ionization. This specific signature peptide is derived from the complementarity-determining region (CDR) of adalimumab. A quadratic regression (weighted 1/concentration), with an equation y = ax(2) + bx + c, was used to fit calibration curves over the concentration range of 1–100 μg/mL for adalimumab. The qualification run met the acceptance criteria of ±25% accuracy and precision values for quality control (QC) samples. This qualified LC-QTOF-MS/MS method was successfully applied to a pharmacokinetic study of adalimumab in rats as a case study. This LC-QTOF-MS/MS approach would be useful as a complementary method for adalimumab or its biosimilars at an early stage of research.